The Effect of Game Based Learning and Perfect Ear on Learning Concentration In Reading Rhythmic Notation - Bertina, Metha; Udi Utomo; Syahrul Syah Sinaga; Suharto Suharto; Wandah Wibawanto (Universitas Negeri Semarang, 2024)
The learning of Art Music in Junior High School can be conducted in various ways, one of which is the use of innovative media. One of these innovative media is Perfect Ear as an Android application used to train aural skills and musical taste in a person who is eager to learn about music theory, specifically rhythmic training. Perfect Ear has been widely played and uploaded by a large number of people. This study aims to measure the effect of Perfect Ear on students' learning concentration level. The method used in this research is Classroom Action Research with a Quantitative approach and using statistical analysis (SPSS). The results showed that the independent variables X1: Game Based Learning, X2: Perfect Ear, and X3: Reading rhythmic notation have a correlation with each other on the dependent variable Y: Learning Concentration. Here are the research results: 1) Game Based Learning is 95% proven to significantly affect the level of learning concentration, 2) Perfect Ear is also proven by 95% in influencing the level of concentration, 3) Reading rhythmic notation has no influence on the level of learning concentration, but 4) Game Based Learning, Perfect Ear, and reading rhythmic notation have a 95% influence on the level of learning concentration when they are combined. And in the final measurement, the R Squared value is 31.80%, which means that the total percentage of the effectiveness of the independent variables (X1, X2, X3) on the dependent variable (Y) is smaller than the total percentage derived from other independent variables